Associations between adverse childhood experiences, attitudes towards COVID-19 restrictions and vaccine hesitancy: a cross-sectional study. Issue 2 (1st February 2022) - Bellis, Mark A; Hughes, Karen; Ford, Kat; Madden, Hannah C E; Glendinning, Freya; Wood, Sara
Abstract : Objectives: Adverse childhood experiences (ACEs) can affect life-course health and well-being, including risk-taking behaviour and trust. This study explored associations between ACEs and trust in health information on COVID-19, attitudes towards and compliance with COVID-19 restrictions and vaccine hesitancy. Design: National cross-sectional telephone survey using a sample of landline and mobile numbers stratified by Health Board, deprivation quintile and age group. Setting: Households in Wales during national COVID-19 restrictions (December 2020 to March 2021). Participants: 2285 Welsh residents aged ≥18 years. Measures: Nine ACEs; low trust in National Health Service (NHS) COVID-19 information; supporting removal of social distancing and mandatory face coverings; breaking COVID-19 restrictions; and vaccine hesitancy (rejection or uncertainty of vaccination). Results: Increasing ACE counts were independently related to low trust in NHS COVID-19 information, feeling unfairly restricted by government and ending mandatory face coverings. High ACE counts (4+ vs 0 ACEs) were also associated with supporting removal of social distancing. Breaking COVID-19 restrictions increased with ACE count with likelihood doubling from no ACEs to 4+ ACEs. Vaccine hesitancy was threefold higher with 4+ ACEs (vs 0 ACEs) and higher in younger age groups. Thus, modelled estimates of vaccine hesitancy ranged from 3.42% with no ACEs, aged ≥70 years, to 38.06% with 4+ ACEs, aged 18–29 years. Conclusions: ACEs are common across populations of many countries. Understanding how they impact trust in health advice and uptake of medical interventions could play a critical role in the continuing response to COVID-19 and controlling future pandemics. Individuals with ACEs suffer greater health risks throughout life and may also be excluded from interventions that reduce infection risks. While pandemic responses should consider how best to reach those suffering from ACEs, longer term, better compliance with public health advice is another reason to invest in safe and secure childhoods for all children.